Seasonal succession of gelatinous zooplankton (medusae and ctenophores) from Mar del Plata harbor, Argentina (SW Atlantic Ocean) - Puente Tapia, Francisco Alejandro (2019)
Temporal variation of the population dynamics of the medusae and ctenophores (gelatinous zooplankton) is described over an annual cycle in the Mar del Plata Harbor, Argentina. A total of 18 species was identified, three of which were ctenophores (two of Class Tentaculata and one of Nuda) and 15 medusae (14 of Class Hydrozoa and one of Scyphozoa). A species of hydromedusae, Annatiara affinis, was observed for the first time in the Argentine Sea. In both groups, species richness and abundances showed clear seasonality, with the lowest values in the cold period (austral autumn-winter) and the highest values in the warm period (spring-summer). The meroplanktonic medusae Obelia sp. and Eucheilota ventricularis as well as the holoplanktonic Liriope tetraphylla represented 94.2% of the total abundances of this group (classified as dominant). In the ctenophores, the dominant species were Pleurobrachia pileus and Mnemiopsis leidyi, which accounted for 99.3% of the ctenophores. Monthly medusae succession indicated that holoplanktonic species were dominant over practically all the annual cycle in terms of abundance, while considering species richness values, meroplanktonic species dominated. Ctenophores (considering abundance values) was displayed alternating periods of approximately three months of dominance between P. pileus and M. leidyi. The Bray-Curtis similarity index performed on medusae identified two groups of seasons with faunal affinity, the 1) cold and 2) warm periods, with the water temperature and non-gelatinous zooplankton abundances as the environmental factors that best explained this variability (BIO-ENV analysis), while for ctenophores, temporal faunal homogeneity was observed and a single group with faunal affinity was identified.